Australia's Antarctic Agenda - Marcus Haward; Rothwell, DR; Julia Jabour; Harold Hall; Aynsley Kellow; Kriwoken, LK; Gail Lugten; Hemmings, A (2006)
Australia has had a long connection with, and significant national interests in, the Southern Ocean and Antarctica. The Australian Antarctic Territory comprises 42 per cent of Antarctica's landmass. Australia is not only a claimant state and original signatory to the Antarctic Treaty but has played a significant role in the development of what is termed the Antarctic Treaty System (ATS). This article aims to provide an overview of Australia's key policy interests and government policy goals towards Antarctica, including its commitment to the ATS. In examining key policy objectives we note that despite continuity and development of these objectives, significant changes and challenges have arisen in the period 1984-2006. It is these challenges that will help frame Australia's Antarctic agenda over the next 20 years and beyond.